2011
DOI: 10.4236/eng.2011.310128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Infrared Thermography for On-Line Condition Monitoring of Rotating Machines

Abstract: This study evaluated the possibility of infrared thermography to measure accurately the temperature of elements of a rotating device, within the scope of condition monitoring. The tested machine was a blower coupled to a 500 kW electric motor, that operated in multiples regimes. The thermograms were acquired by a fixed thermographic camera and were processed and recorded every 15 minutes. Because the normal temperature variations could easily mask a drift caused by a failure, a corrected temperature was comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…[32][33][34] Further requirements include the presence of a thermally controlled environment, the proper preparation and orientation of the person who will undergo analysis, and the standardization of the technique with respect to the intervals of analysis, and completion of independent instruments by investigators. 13,17,20…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34] Further requirements include the presence of a thermally controlled environment, the proper preparation and orientation of the person who will undergo analysis, and the standardization of the technique with respect to the intervals of analysis, and completion of independent instruments by investigators. 13,17,20…”
Section: Discussionmentioning
confidence: 99%
“…The testing environment was thermally controlled at a constant temperature of 23°C. 17,20 To obtain stable interpretations of plantar temperature and to prevent that the temperature of other parts of the body interfering on the photographic record, the feet were thermally insulated by a uniform backdrop. 18 This uniform backdrop consisted in a box with 2 openings for the feet.…”
Section: Photographic Recordmentioning
confidence: 99%
“…Problems with bearings are usually found by comparing the surface temperatures of similar bearings working under similar conditions. Overheating conditions appear as ''hot spots'', within an infrared image as usually found by comparing similar equipment [4].…”
Section: Introductionmentioning
confidence: 93%
“…The result of this study showed that thermography could assist in detecting the abnormal operation of various components at an early stage of impending failure. Leemans et al [10] evaluated the possibility of IRT to online monitor the element temperatures of an industrial blower, which included a 500 kW electric motor, a drive motor bearing, and two bearings supporting the blower, to detect wear or other defects. In fault diagnosis, thermogram was used by Younus et al [11].…”
Section: Infrared Thermography (Irt) Is a Non-contact And Non-destrucmentioning
confidence: 99%